Pemodelan dan simulasi reverse flow reactor untuk oksidasi katalitik metana: pengembangan prosedur operasi start-up - Yogi Wibisono Budhi; Teguh Kurniawan; Yazid Bindar (Jurnal Teknik Kimia Indonesia, 2011)
Modeling and simulation of reverse flow reactor for the catalytic oxidation of methane: the development of start-up operating procedures In this modelling and simulation study, three operating procedures during start-up of lean methane (1%-v) oxidation in reverse flow reactor (RFR) have been investigated to get auto-thermal condition, high methane conversion, faster pseudo steady state, and low preheating energy requirement. The RFR model developed based on one-dimension pseudo-homogeneous model for mass balance and heterogeneous model for energy balance. Procedure 1 , the preheating was employed only on the catalyst zone, fails to conduct the auto-thermal reaction and to achieve high conversion. Procedure 2, the preheating was employed for inert and catalyst of left side only, able to achieve the auto-thermal up to switching time (ST) 230 s. Procedure 3, the preheating was employed along the reactor bed, achieve the auto-thermal condition up to ST 300 s. Procedure 2 and 3 achieved the pseudosteadystate at 1000 s for ST 200 s with total conversion during start-up are 95% and 99%. The conversion of Procedure 3 higher than Procedure 2, unfortunately the heat load of Procedure 3 two times higher than Procedure 2. Keywords: modelling and simulation, catalytic methane oxidation, start-up procedure, reverse flow reactor, switching timeAbstrakDi dalam studi pemodelan dan simulasi ini, berbagai prosedur operasi reverse flow reactor (RFR) selama start-up untuk oksidasi katalitik metana encer (1%-v) dikaji dengan target sistem beroperasi secara ototermal, konversi metana tinggi, waktu pencapaian kondisi tunak semu (pseudosteady state) cepat, dan beban panas rendah. Pemodelan reaktor didasarkan pada model satu dimensi dan pseudohomogeneous untuk neraca massa, serta heterogen untuk neraca energi. Pemanasan katalis saja pada awal reaksi (Prosedur 1) tidak dapat mencapai kondisi reaktor yang ototermal. Pemanasan katalis dan inert bagian kiri (Prosedur 2) mampu mencapai kondisi reaktor yang ototermal hingga switching time (ST) 230 detik. Pemanasan seluruh bagian reaktor pada awal reaksi (Prosedur 3) mampu mencapai kondisi reaktor yang ototermal pada ST paling lama 300 detik. Prosedur start-up 2 dan 3 untuk ST 200 detik sama-sama mencapai waktu pseudosteady state pada 1000 detik dengan konversi total selama start-up masing-masing 95% dan 99%. Meskipun Prosedur 3 memberikan konversi sedikit lebih tinggi daripada Prosedur 2, namun beban panas Prosedur 3 mencapai dua kali lebih besar daripada Prosedur 2.Kata kunci: emisi metana, pemodelan dan simulasi, prosedur start-up, reverse flow reactor, switching time.